Chronic post-traumatic headache in pediatrics. (July 2014) - Abu-Arafeh, Ishaq; Howells, Rachel
SUMMARY : Both primary headaches and minor head injuries are common in children. If headache presents for the first time or becomes exacerbated soon after head injury it is described as post-traumatic headache (PTH). Acute PTH resolves within 3 months from injury, but chronic PTH continues beyond 3 months. The pathogenesis of PTH is not well understood. Several mechanisms were proposed such as axonal injuries and disturbances of cerebral metabolic processes. The clinical features of PTH are those of primary headache disorders such as migraine and tension-type headache and usually follow a favorable prognosis. Investigations and management should therefore be relevant to the type of headache and focused on clinical needs of the child.